Identification of "sleeping" talent using psychological characteristics in junior elite ice-hockey players - Fortin-Guichard, D.; Tétreault, É.; Paquet, D.; Mann, D. L.; Grondin, S. (Journal of Sports Sciences, 2023)
Scouts search for "sleepers" who may be initially overlooked but ultimately exceed expectations. The psychological characteristics of those players are often neglected because they are difficult to observe, but hold promise to identify sleepers given for example the self-regulation and perceptual-cognitive skills that those developing players might need to flourish. The aim of this study was to examine whether sleepers could be retrospectively identified using psychological characteristics. Ninety-five junior elite ice-hockey players (aged 15-16) were assessed on self-regulation and perceptual-cognitive skills before the yearly draft. Seventy players were drafted after the second round (37th or later). Three years later, professional scouts identified 15/70 sleepers they would now pick if given the chance. Those identified by the scouts showed higher self-regulation planning, and had distinguishable gaze behaviour (fewer fixations on more AOIs) when performing a video-based decision-making task than other late-drafted players (84.3% correct classification; R2 = .40). In addition, two latent profiles differentiated by self-regulation were found, with the profile with higher scores including 14/15 players selected by the scouts. Psychological characteristics were successful in retrospectively predicting sleepers, and may in future help scouts to make better selections of talent.